Characterization and forensic identification of a novel cocaine charcoal smuggling matrix. (January 2022) - Bretler, Uriel; Shimron, Simcha; Bretler, Sharon; Yizhakov, Yafit
Highlights: Sacks filled with charcoal-like material were seized during a smuggling attempt. Initial tests (field kit and IR) indicated the presence of cocaine in the seizure. Quantitative analyses of some samples revealed high cocaine content percentage. Morphology and composition of the different matrixes were analyzed by SEM-EDX. TGA measurements support the results of high cocaine content within the material. Abstract: Every year new and sophisticated drug-smuggling methods are encountered by law enforcement agencies all over the globe. A seized cross-border smuggling attempt was found to contain charcoal. This unexpected smuggling cargo raised doubts as to the real content of the material. Initial testing indicated that the black charcoal-like material contained cocaine. The material was forensically tested for cocaine presence and quantitatively analyzed for cocaine concentration. Initial testing with an illicit substance identification field kit and FTIR revealed that some of the material contained cocaine whereas other pieces were completely free of cocaine. Cocaine-containing material was quantitatively measured and was found to consist of over 50% cocaine. In addition, the morphology and element composition of the suspected matrix were analyzed by SEM and EDX. The results pointed to some structural and composition differences between material loaded with cocaine and charcoal free of the drug. One of the most significant and surprising differences in the element composition measurements was the finding of iron in the cocaine-containing material. Moreover, thermogravimetric analysis was performed on the samples to support the material composition analyses. Although the exhibits did not display a homogenous presence and concentration of cocaine, the porous morphological structure and the high cocaine concentration in some of the samples reveal that the carbon-rich matrix has a potential for high capacity drug uptake. The iron accompanying the cocaine is probably a left over product of the cocaine masking process.